Furlough unemployment - Heikki Korpela (Helsinki Graduate School of Economics, 2024)
I examine the long-established scheme of furloughs in Finland, using detailed data on unemployment spells from 1999 to 2021. Furloughs allow employers in financial difficulty to suspend wages and work while retaining the job contract. They con-stituted the majority of new UI spells during the economic crises in 2009 and 2020. Most furloughs end quickly with a return to regular work, and they are only weakly associated with later permanent dismissals or firm survival. Despite widespread use in crisis years, more than half of the cumulative furlough benefits over the two decades were collected by only a few percent of the population. This group was furloughed five times or more over the observed period, often by the same employer. The patterns suggest that furloughs have a dual role: as a short-term safety net in recessions for most employers and as a regular business practice in normal times in a few industries.
Keywords: J23; J33; J63; J68; 330; temporary unemployment; furloughs; recall